Genotypic and Lipid Analyses of Strains From the Archaeal Genus Halorubrum Reveal Insights Into Their Taxonomy, Divergence, and Population Structure - de la Haba, Rafael R.; Corral, Paulina; Sánchez-Porro, Cristina; Infante-Domínguez, Carmen; Makkay, Andrea M.; Amoozegar, Mohammad A.; Ventosa, Antonio; Papke, R. Thane (Frontiers in Microbiology, 2018)
To gain a better understanding of how divergence occurs, and how taxonomy can benefit from studying natural populations, we isolated and examined 25 closely related Halorubrum strains obtained from different hypersaline communities and compared them to validly named species and other reference strains using five taxonomic study approaches: phylogenetic analysis using the 16S rRNA gene and multilocus sequencing analysis (MLSA), polar lipid profiles (PLP), average nucleotide identity (ANI) and DNA-DNA hybridization (DDH). 16S rRNA gene sequence could not differentiate the newly isolated strains from described species, while MLSA grouped strains into three major clusters. Two of those MLSA clusters distinguished candidates for new species. The third cluster with concatenated sequence identity equal to or greater than 97.5 % was comprised of strains from Aran-Bidgol Lake (Iran) and solar salterns in Namibia and Spain, and two previously described species isolated from Mexico and Algeria. PLP and DDH analyses showed that Aran-Bidgol strains formed uniform populations, and that strains isolated from other geographic locations were heterogeneous and divergent, indicating that they may constitute different species. Therefore, applying only sequencing approaches and similarity cutoffs for circumscribing species may be too conservative, lumping concealed diversity into a single taxon. Further, our data support the interpretation that local populations experience unique evolutionary homogenization pressures, and once relieved of insular constraints (e.g., through migration) are free to diverge.